2006
DOI: 10.1002/ppsc.200601020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mechanical Resistance of a Powder‐powder Coating by Modulated Dry Feed Particle Size Analysis

Abstract: Dry powder coating is a powerful method for modifying the surface properties of particles whilst retaining their essential bulk properties. The coating of a host powder by guest particles can be achieved via different means ranging from simple stirring together of the two components, to high energy impact coating in devices such as a Nara Hybridizer or Turbula Mixer. The quality of the powder coating resulting from such methods is an important parameter, which depends both on the force of the mechanical action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…It has also been used successfully as a means to assess the extent and efficacy of fine particle coatings in a dry powder process. 47 In general, the dispersibility of a powder can be derived by comparing the slope of the plot of the particle size with respect to dispersion pressure, where smaller absolute slopes indicate better dispersibility and larger ones indicate worse dispersibility. 48 The pressure titrations of the 5 :m uncoated and dry-coated ibuprofen samples are shown in Figure 3 as an example, because finest powders are expected to be more cohesive and agglomerated.…”
Section: Bulk Level Characteristicsmentioning
confidence: 99%
“…It has also been used successfully as a means to assess the extent and efficacy of fine particle coatings in a dry powder process. 47 In general, the dispersibility of a powder can be derived by comparing the slope of the plot of the particle size with respect to dispersion pressure, where smaller absolute slopes indicate better dispersibility and larger ones indicate worse dispersibility. 48 The pressure titrations of the 5 :m uncoated and dry-coated ibuprofen samples are shown in Figure 3 as an example, because finest powders are expected to be more cohesive and agglomerated.…”
Section: Bulk Level Characteristicsmentioning
confidence: 99%
“…[1]Yoshihara I., Pieper W., Hybridization -Technology for surface modification of powders without binders, Swiss Pharma, 21,6,1999 [2]Pfeffer R., Dave R. N., Dongguang W., Ramlakhan, M., Synthesis of engineered particulates with tailored properties using dry particle coating, Powder Technology, 117, 40-67, 2001…”
Section: Referencesmentioning
confidence: 99%
“…[19] Munjumbar [20] or more recently by Vilela and al. [21]. One of the important points that appeared in these works is the characterisation of the coated product in terms of quantity and quality of the coating.…”
Section: Introductionmentioning
confidence: 99%
“…The method can be qualitative and comparative concerning the coating strength. Indeed, Vilela et al [32] demonstrated that an increase of dispersion pressure can lead to removal of guest particles on the host particles surface. In this work, two levels of dispersion pressures were used: 0.5 and 3.5 bar.…”
Section: Particle Size Distributionmentioning
confidence: 99%